A lightweight PLA composite material, a method for preparing the same and a method for printing a 3D product

CN123004100APending Publication Date: 2026-10-30GUANGDONG SANLV TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610949171.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种轻质PLA复合材料及其制备方法和打印3D产品的方法,从而解决现有技术中需降低挤出流量比例才能制得轻质PLA 3D打印产品的技术难题

Benefits of technology

本发明提供的一种用于3D打印的轻质PLA复合材料,无需调节流量,正常参数即可打印出具有明显减重效果的模型,且发泡可控,不受打印温度影响,发泡稳定;打印3D产品时,打印效果好,表面不拉丝,不堆料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123004100A_ABST
    Figure CN123004100A_ABST
Patent Text Reader

Abstract

The application discloses a kind of lightweight PLA composite material and its preparation method and the method of printing 3D product, it is related to 3D printing technical field.It includes the following mass percentage of raw materials: 90%-95% polylactic acid, 2%-5% modified expansion microsphere foaming master batch, 0.3%-0.8% antioxidant and 2%-5% plasticizer, antioxidant includes hindered phenol antioxidant 1010 and phosphite antioxidant 168.The lightweight PLA composite material provided by the application can print out a model with obvious weight loss effect without adjusting flow, and the foaming is controllable, is not affected by printing temperature, and the foaming is stable;When printing 3D product, the printing effect is good, the surface is not drawn, and the material is not stacked.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of 3D printing technology, and more specifically, to a lightweight PLA composite material, a method for preparing the same, and a method for printing 3D products. Background Technology

[0002] Currently, the available PLA lightweight consumables on the market have a density greater than 1 g / cm³. 3 Printing at normal flow rates yields no significant weight reduction regardless of high or low temperatures; a reduction in printhead flow rate is necessary to achieve substantial weight reduction. Therefore, existing lightweight PLA consumables on the market require a reduction in flow rate ratio to achieve weight reduction, presenting the challenge that the lightweight PLA consumables themselves do not actually reduce weight. Developing lightweight PLA consumables and their manufacturing technologies that inherently reduce weight without requiring a reduction in flow rate is of great significance.

[0003] In view of this, the present invention is proposed. Summary of the Invention

[0004] The purpose of this invention is to provide a lightweight PLA composite material, its preparation method, and a method for printing 3D products, thereby solving the technical problem in the prior art that requires reducing the extrusion flow rate ratio to obtain lightweight PLA 3D printed products.

[0005] This invention is implemented as follows: In a first aspect, the present invention provides a lightweight PLA composite material for 3D printing, comprising the following raw materials by mass percentage: 90%-95% polylactic acid, 2%-5% modified expanded microsphere foaming masterbatch, 0.3%-0.8% antioxidant and 2%-5% plasticizer, wherein the antioxidant includes hindered phenolic antioxidant 1010 and phosphite antioxidant 168; the modified expanded microsphere foaming masterbatch is prepared by surface treatment of foamed microspheres with KH-550 silane coupling agent.

[0006] Secondly, the present invention also provides a lightweight PLA composite material for 3D printing, comprising the following raw materials by mass percentage: 75%-85% polylactic acid, 2%-5% modified expanded microsphere foaming masterbatch, 0.3%-0.8% antioxidant, 5%-15% elastomer, and 2%-5% plasticizer; the antioxidant includes hindered phenolic antioxidant 1010 and phosphite antioxidant 168; the modified expanded microsphere foaming masterbatch is prepared by surface treatment of foamed microspheres with KH-550 silane coupling agent.

[0007] Thirdly, the present invention also provides a method for preparing a lightweight PLA composite material for 3D printing, which includes the following steps: mixing various raw materials and extruding and drawing them into fibers using a screw extruder.

[0008] Fourthly, the present invention also provides a method for printing 3D products using the FDM method, wherein the PLA composite material prepared by the above preparation method is introduced into an FDM 3D printing device and printed directly without a preheating chamber or a closed printing chamber, with a nozzle temperature of 190-220℃, a heated bed temperature of 55±1℃, and an extrusion flow rate of 0.91-0.98 g / s for the PLA composite material.

[0009] The present invention has the following beneficial effects: This invention provides a lightweight PLA composite material for 3D printing. It can print models with significant weight reduction effects without adjusting the flow rate and with normal parameters. The foaming is controllable, unaffected by printing temperature, and the foaming is stable. When printing 3D products, the printing effect is good, and there is no stringing or material accumulation on the surface.

[0010] Specifically, this invention innovatively combines specific types and proportions of foaming agents (foaming masterbatches) and antioxidants, breaking through the limitations of traditional single additives or simple combinations in improving PLA performance. By adding expanded microspheres with double bonds introduced on the surface, the bonding force with the plastic is increased, thus achieving high-performance lightweight PLA consumables.

[0011] This invention also provides a preparation process for PLA consumables specifically designed for lightweight printing, which achieves stable and uniform material output of PLA lightweight consumables during the extrusion process. It effectively solves the problems that traditional PLA lightweight consumables are prone to during printing, such as stringing, material shortage, and the need to reduce printing flow to achieve weight reduction, and greatly improves printing efficiency and molding quality.

[0012] This invention achieves a good balance between thermal stability, melt flowability and mechanical properties through precise control of each step. This makes the PLA lightweight consumable not only suitable for printing with ordinary parameters, but also has sufficient strength and toughness after printing, which can be widely used in a variety of fields, thus expanding the application scope of PLA lightweight consumables in the field of 3D printing. Attached Figure Description

[0013] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0014] Figure 1 This image shows the surface quality of a 3D-printed model using modified expanded microspheres.

[0015] Figure 2This image shows the surface quality of a 3D-printed model using unmodified expanded microspheres. Detailed Implementation

[0016] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0017] This project will delve into the lightweight properties of PLA, carefully selecting and formulating additives to ensure the material itself is low-density, guaranteeing that printing at normal flow rates will result in a significant weight reduction in the model. Simultaneously, it will focus on balancing the changes in mechanical properties during material modification to ensure the printed product possesses good mechanical strength and toughness, making it suitable for high-speed 3D printing of more complex structures and functional components. This will improve the efficiency and application scope of 3D printing in industrial production, scientific research, and other fields, powerfully promoting the technological progress and development of the 3D printing industry.

[0018] In a first aspect, the present invention provides a lightweight PLA composite material for 3D printing, comprising the following raw materials by mass percentage: 90%-95% polylactic acid, 2%-5% modified expanded microsphere foaming masterbatch, 0.3%-0.8% antioxidant and 2%-5% plasticizer, wherein the antioxidant includes hindered phenolic antioxidant 1010 and phosphite antioxidant 168; the modified expanded microsphere foaming masterbatch is prepared by surface treatment of foamed microspheres with KH-550 silane coupling agent.

[0019] This invention discovers a synergistic composite modification system of modified expandable microsphere foaming masterbatch and antioxidants: the expandable microsphere foaming masterbatch is surface-treated with silane coupling agent KH-550, and then compounded with hindered phenolic antioxidant 1010 and phosphite antioxidant 168 to form a thermally stable and stress-buffering bifunctional filler. This composite filler significantly inhibits the thermal degradation of PLA within the above-mentioned addition range (T5₋d compared to unmodified foaming masterbatch). a The temperature was increased to 342℃, and the thermal stress gradient during the cooling process was reduced, resulting in a 62% reduction in warpage height. This synergistic mechanism breaks through the limitation of traditional single fillers that only improve one aspect of performance, and for the first time achieves simultaneous enhancement of thermal stability and thermal stress buffering.

[0020] In the compound of modified expandable microsphere foaming masterbatch and antioxidant (i.e. filler), the expandable microsphere foaming masterbatch undergoes silane coupling treatment to achieve hydroxyl grafting on the surface of the expandable microspheres, thereby enhancing the interfacial bonding with the PLA matrix.

[0021] With the addition of 2%-5% modified expanded microsphere foaming masterbatch and 0.3%-0.8% antioxidant, thermal stability (T5₋d) is simultaneously improved. a With a temperature of up to 342℃ and stress buffering capacity, the weight reduction effect reaches 10-40%, breaking through the limitations of low strength and functionality of lightweight consumables.

[0022] The synergistic effect of modified expanded microsphere foaming masterbatch and antioxidant stems from the low coefficient of thermal expansion of the modified expanded microsphere foaming masterbatch (≈4×10⁻). 6 The physical-chemical coupling of / K) with the endothermic thermal decomposition properties of antioxidants: the modified expandable microsphere foaming masterbatch slows down the local shrinkage rate during the cooling stage, while the antioxidant inhibits free radical chain degradation. Together, they mitigate the spatiotemporal asynchrony of the temperature field and the stress field.

[0023] In one alternative embodiment, the modified expanded microsphere foaming masterbatch and antioxidant are preferably added at a mass ratio of 5% of the total raw materials, in which case T5₋d a The temperature reaches a peak of 342℃ and the weight loss effect reaches 40%, at which point the weight loss effect is even better.

[0024] When the added amount of modified expanded microsphere foaming masterbatch and antioxidant is not 5% of the total raw material mass, the interfacial compatibility decreases or the melt viscosity surges. Decreasing the amount of foamed microspheres will, to some extent, increase interlayer bonding strength, but weaken the weight reduction effect. In one embodiment, those skilled in the art can adaptively select the added amount of modified expanded microsphere foaming masterbatch and antioxidant that achieves the optimal weight reduction effect as needed. Alternatively, an added amount of modified expanded microsphere foaming masterbatch and antioxidant that balances interlayer bonding strength and weight reduction can be selected.

[0025] The bifunctional composite filler of the present invention, which is composed of KH-550 surface-modified expanded microsphere foaming masterbatch and antioxidant 1010 / 168, is different from conventional single antioxidant or single filler systems. Its core lies in achieving directional grafting of hydroxyl groups on the surface of the expanded microsphere foaming masterbatch through silane coupling, simultaneously endowing it with interfacial compatibility and thermo-mechanical synergistic response capability. This filler does not require the additional synthesis of new compounds, and can achieve a leap in performance simply through physical compounding and controllable surface treatment. The process is simple, the cost is controllable, and it is easy to scale up for industrialization.

[0026] In one alternative embodiment, the amount of modified expanded microsphere foaming masterbatch and antioxidant added includes, but is not limited to, the following combination: 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5% of modified expanded microsphere foaming masterbatch and 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or 0.8% of antioxidant.

[0027] In a preferred embodiment of the present invention, the surface treatment conditions include: treatment at 60°C-80°C for 2-3 hours in a system with an ethanol:water volume ratio of 9:1, and a solid-liquid ratio of 1:8 between the foamed microspheres and the KH-550 silane coupling agent. In one embodiment, the in-situ surface modification process of the silane coupling agent in the modified expanded microsphere foaming masterbatch involves using KH-550 in an ethanol / water (9:1 v / v) system, reacting at a constant temperature of 80°C for 2 hours, with the concentration precisely controlled at 2.5 wt%. These conditions result in an amino grafting rate of 91.3% on the microsphere surface, a 22.7% increase compared to the conventional 60°C process, and an increase in interfacial bonding energy from 1.87 J / m² to 2.95 J / m². This modification not only significantly enhances the synergistic effect of hydrogen and covalent bonds between the microspheres and the PLA matrix but also endows them with a directional thermal stress buffering function.

[0028] In one embodiment, the modified expanded microsphere foaming masterbatch was purchased from Jieshangjie, item number T-700-40S.

[0029] In a preferred embodiment of the present invention, the foamed microspheres are selected from polypropylene expanded microsphere foaming masterbatch, polyethylene masterbatch, polyvinyl chloride masterbatch, EVA, POE, TPR, TPV or TPU.

[0030] In a preferred embodiment of the present invention, the mass ratio of hindered phenolic antioxidant 1010 to phosphite antioxidant 168 is (1-3):2; for example, 1:2, 2:2 or 3:2.

[0031] In a preferred embodiment of the present invention, the mass ratio of the modified expanded microsphere foaming masterbatch to the hindered phenolic antioxidant 1010 and the phosphite antioxidant 168 is 100:3:2.

[0032] In a preferred embodiment of the present invention, the raw materials of the PLA composite material also include a lubricant; the mass percentage of the lubricant in the raw materials is 0.5% ± 0.1%.

[0033] In a preferred embodiment of the present invention, the raw materials of the PLA composite material further include 0.3% ± 0.05% of an antioxidant synergist; the antioxidant synergist is preferably Irganox 1076.

[0034] In a preferred embodiment of the present invention, the plasticizer is selected from ATBC.

[0035] Lightweight PLA composites without elastomers exhibit poor brittleness, while lightweight PLA composites prepared with elastomer raw materials demonstrate superior toughness. Those skilled in the art can adaptively add elastomers as needed.

[0036] The lubricants are selected from: stearate metal soaps (calcium stearate, zinc stearate, magnesium stearate, barium stearate), amide / wax lubricants (erucamide, oleamide, ethylene bis-stearamide (EBS)), organic acids and polymer waxes.

[0037] Secondly, the present invention also provides a lightweight PLA composite material for 3D printing, comprising the following raw materials by mass percentage: 75%-85% polylactic acid, 2%-5% modified expanded microsphere foaming masterbatch, 0.3%-0.8% antioxidant, 5%-15% elastomer, and 2%-5% plasticizer; the antioxidant includes hindered phenolic antioxidant 1010 and phosphite antioxidant 168; the modified expanded microsphere foaming masterbatch is prepared by surface treatment of foamed microspheres with KH-550 silane coupling agent.

[0038] In a preferred embodiment of the present invention, the mass ratio of hindered phenolic antioxidant 1010 to phosphite antioxidant 168 is (1-3):2; the combination of the two can produce a good synergistic effect, which is far better than using one of them alone.

[0039] In a preferred embodiment of the present invention, the mass ratio of the modified expanded microsphere foaming masterbatch to the hindered phenolic antioxidant 1010 and the phosphite antioxidant 168 is 100:3:2. This mixing mass ratio results in a superior weight reduction effect.

[0040] In other embodiments, the mass ratio of the modified expanded microsphere foaming masterbatch to the hindered phenolic antioxidant 1010 and the phosphite antioxidant 168 includes, but is not limited to, 99-101:3:2.

[0041] In a preferred embodiment of the present invention, the elastomer is selected from thermoplastic polyurethane elastomers, natural rubber and its epoxidized modified forms, styrene-based thermoplastic elastomers, bio-based copolyester elastomers (PLBSIs), polycaprolactone (PCL), or polybutylene succinate (PBS).

[0042] In a preferred embodiment of the present invention, the raw materials of the PLA composite material also include a lubricant; the mass percentage of the lubricant in the raw materials is 0.5% ± 0.1%.

[0043] In a preferred embodiment of the present invention, the raw materials of the PLA composite material further include 0.3% ± 0.05% of an antioxidant synergist; the antioxidant synergist is preferably Irganox 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, CAS No. 2082-79-3); as a highly efficient and non-discoloring primary antioxidant, its core function is to provide long-term thermal stability to polymer materials by capturing free radicals, protecting the materials from thermal oxidative degradation during long-term use.

[0044] In a preferred embodiment of the present invention, the plasticizer is selected from ATBC (acetylsicottol tributyl ester).

[0045] Thirdly, the present invention also provides a method for preparing a lightweight PLA composite material for 3D printing, comprising the following steps: The raw materials are mixed and then extruded into fibers using a screw extruder.

[0046] In a preferred embodiment of the present invention, after the raw materials are melt-blended, water-cooled and granulated, the resulting granules are vacuum-dried, and then melt-blended and water-cooled and drawn into fibers using a single-screw extruder.

[0047] In a preferred embodiment of the present invention, the various raw materials are mixed and then melt-blended using a twin-screw extruder. The length-to-diameter ratio of the screw is 35-95, the temperature range is 180℃-220℃, and the die temperature is 200-220℃. The length-to-diameter ratio of the screw is 35, 52, 65, 75, or 95.

[0048] Vacuum dried at 80℃ for 4 hours; melt-blended using a single-screw extruder with a screw length-to-diameter ratio of 45, temperature range of 180℃-220℃, die temperature of 220℃, and water-cooled drawing.

[0049] Fourthly, this invention also provides a method for FDM printing of 3D products. The PLA composite material prepared by the above method is introduced into an FDM 3D printing device and printed directly without a preheating chamber or a sealed printing chamber. The nozzle temperature is 190-220℃, the heated bed temperature is 55±1℃, and the extrusion flow rate of the PLA composite material is 0.91-0.98 g / s. The extrusion flow rate is the mass of melt extruded per unit time. Examples of extrusion flow rates include 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, or 0.98 g / s.

[0050] The PLA composite material provided by this invention, as verified by experiments, under nozzle temperatures of 190-220℃ and a heated bed of 55℃, achieves a 40% weight reduction compared to ordinary PLA printing when printing cubic blocks (100×100×100mm standard parts) at normal PLA extrusion flow rates. It also exhibits good surface finish, with no material shortage or accumulation. The printing speed is stably supported at 100-200mm / s.

[0051] The modified expanded microsphere foaming masterbatch was surface-modified with KH-550 silane coupling agent (concentration 2.5wt%, ethanol / water = 9:1, isothermal reaction at 60℃ for 2h), which improved its interfacial compatibility with the PLA matrix by 47% (contact angle decreased from 82° to 43°). Simultaneously, a dual mechanism of "rigid cavity buffer + free radical capture" was constructed: the hollow structure (particle size 20–45μm, wall thickness 0.5–1.2μm) physically absorbs thermal stress, while antioxidant 1010 / 168 (mass ratio 100:3:2) chemically inhibits high-temperature oxidative degradation. The synergistic effect increased the T5% thermal weight loss temperature from 298℃ to 342℃ and the thermal decomposition activation energy by 21.6 kJ / mol. This synergistic effect resulted in a melt strength retention rate of ≥92% and an interlaminar shear strength of 28.7 MPa (a 39.2% improvement compared to the unmodified control group) under normal foaming extrusion (100-200mm / s).

[0052] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0053] Example 1 This embodiment provides a lightweight PLA composite material for 3D printing, which comprises the following raw materials by mass percentage: 75.0±0.2 wt% PLA (Fengyuan 802), 15.0±0.3 wt% thermoplastic polyurethane elastomer (BASF), 5.0±0.1 wt% bifunctional composite filler (expanded microsphere foaming masterbatch in situ amination at 80℃ / 2h / 2.5wt% using KH-550, then mechanically blended with antioxidant 1010 / 168 at a mass ratio of 100:3:2), 4.5±0.1 wt% plasticizer (ATBC), with the balance being lubricant (calcium stearate 0.5±0.1 wt%) and antioxidant synergist (Irganox 1076 0.3±0.05 wt%).

[0054] The modified expanded microsphere foaming masterbatch in this embodiment was purchased from Jieshangjie, item number T-700-40S.

[0055] The method for preparing lightweight PLA composite materials is as follows: The mixture consists of 75.0±0.2 wt% PLA, 15.0±0.3 wt% thermoplastic polyurethane elastomer, 5.0±0.1 wt% bifunctional composite filler (expanded microsphere foaming masterbatch in situ amination at 80℃ / 2h / 2.5wt% using KH-550, followed by mechanical blending with antioxidant 1010 / 168 at a mass ratio of 100:3:2), 4.5±0.1 wt% plasticizer (ATBC), with the balance being lubricant (calcium stearate 0.5±0.1 wt%) and antioxidant synergist (Irganox 1076 0.3±0.05%). Composed of (wt%); after being melt-blended and water-cooled granulated by a twin-screw extruder (L / D=35, temperature range: 180→220℃, die 220℃), the resulting granules were vacuum-dried at 80℃ for 4 hours; and then melt-blended and water-cooled into wires by a single-screw extruder (L / D=45, temperature range: 180→220℃, die 220℃).

[0056] The method for printing 3D products using the FDM method is as follows: Using an FDM 3D printer (Nozle Ø0.4mm, layer thickness 0.2mm), direct printing was performed without a preheating chamber or enclosed printing chamber (nozzle 210±2℃, heated bed 55±1℃). The extrusion flow rate was 0.95 g / s. The measured first-layer adhesion was ≥2.8MPa. At a speed of 100mm / s, the printed model achieved a 40% weight reduction and good surface quality. Figure 1 Interlayer adhesion strength: 6.8 kJ / m 2 Compared with the unmodified expanded microsphere PLA control group, the weight reduction effect was good, but the unmodified expanded microsphere PLA had poor interlayer adhesion and poor surface effect.

[0057] The first-layer adhesion refers to the adhesion to the base plate, while the interlayer adhesion refers to the adhesion between each layer.

[0058] Example 2 This embodiment provides a lightweight PLA composite material for 3D printing, which comprises the following raw materials by mass percentage: PLA matrix 77±0.3 wt%, thermoplastic polyurethane elastomer 13.2±0.2 wt%, silane coupling modified expanded microsphere foaming masterbatch (KH-550, 80℃ / 2h / 2.5wt%) 4.0±0.1 wt%, antioxidant 1010 / 168 / 1076 (1:3:2) 0.8±0.05 wt%, ATBC plasticizer 4.5±0.1 wt%, calcium stearate 0.5±0.1 wt%.

[0059] The preparation process is the same as in Example 1, but the nozzle temperature gradient is optimized to 195→205℃ (increasing for three layers from bottom to top), the printing speed is 100-200 mm / s, the weight reduction is 30%, the first layer adhesion is maintained at 2.75±0.08 MPa, and the interlayer adhesion is 7.3 kJ / m. 2 The printing quality is good.

[0060] Example 3 This embodiment provides a lightweight PLA composite material for 3D printing, which comprises the following raw materials by mass percentage: PLA matrix 92.0±0.3 wt%, silane coupling modified expanded microsphere foaming masterbatch (KH-550, 80℃ / 2h / 3.0wt%) 3.0±0.1 wt%, antioxidant 1010 / 168 (3:2) 0.6±0.05 wt%, ATBC 4.0±0.1 wt%, calcium stearate 0.4±0.1 wt%. This example does not contain elastomers.

[0061] The remaining processes are the same as in Example 1; printing speed is 100-200 mm / s, weight reduction is 20%, first-layer adhesion is maintained at 2.75±0.08 MPa; printing effect is good. Interlayer adhesion is 7.8 kJ / m 2 .

[0062] Example 4 This embodiment provides a lightweight PLA composite material for 3D printing, which comprises the following raw materials by mass percentage: PLA matrix 92.5±0.3 wt%, silane coupling modified expanded microsphere foaming masterbatch (KH-550, 80℃ / 2h / 5.0wt%) 2.0±0.1 wt%, antioxidant 1010 / 168 (masterbatch to antioxidant 1010 / 168 mass ratio is 100:3:2) 0.7±0.05 wt%, ATBC 4.5±0.1 wt%, calcium stearate 0.3±0.1 wt%. This embodiment does not contain elastomers.

[0063] The remaining processes are the same as in Example 1; printing speed is 100-200 mm / s, weight reduction is 10%, first-layer adhesion is maintained at 2.75±0.08 MPa; printing effect is good. Interlayer adhesion is 8.2 kJ / m 2 .

[0064] Comparative Example 1 This comparative example uses unmodified expanded microsphere foaming masterbatch to prepare PLA composite materials.

[0065] Specifically, the raw material composition is as follows: PLA matrix 75.0±0.3 wt%, unmodified expanded microsphere foaming masterbatch (without KH-550 treatment) 5.0±0.1 wt%, antioxidant 1010 / 168 (100:3:2) 0.7±0.05 wt%, ATBC 4.5±0.1 wt%, calcium stearate 0.3±0.1 wt%; the remaining processes are the same as in Example 1; this control group achieved a weight reduction of 40% when printing models at 100-200 mm / s, but the surface finish was poor. Figure 2 As shown in the figure, the interlayer adhesion is poor.

[0066] Comparative Example 2 This comparative example demonstrates the preparation of PLA composite materials without the addition of expanded microsphere foaming masterbatch.

[0067] Specifically, the raw material composition is as follows: PLA matrix 80.0±0.3 wt%, antioxidant 1010 / 168 (100:3:2) 0.7±0.05 wt%, ATBC 4.5±0.1 wt%, calcium stearate 0.3±0.1 wt%; Comparative Example 2 did not add modified expanded microsphere foaming masterbatch, and the rest of the process was the same as in Example 1; This comparative example printed models at 100-200 mm / s, with good printing effect, good interlayer adhesion, and no weight reduction effect.

[0068] Experimental Example 1 This experiment tested the weight reduction effect and interlayer adhesion of models prepared in various embodiments and comparative examples. The results are shown in the table below. The results show that the silane coupling modified expanded microsphere foaming masterbatch has a good weight reduction effect and good interlayer adhesion when printing models at 100-200 mm / s. The modified expanded microspheres have higher dispersibility in resin and better binding force with resin.

[0069] Printing speed 100-200mm / s Printing speed 100-200mm / s Printing speed 100-200mm / s Printing speed 100-200mm / s Printing speed 100-200mm / s Printing speed 100-200mm / s Printing temperature 210℃ Printing temperature 210℃ Printing temperature 210℃ Printing temperature 210℃ Printing temperature 210℃ Printing temperature 210℃ Weight reduction effect: 40%; interlayer adhesion: 6.8 kJ / m² Weight reduction effect of 30%; interlayer adhesion strength of 7.3 kJ / m2 Weight reduction effect: 20%; interlayer adhesion: 7.8 kJ / m² Weight reduction effect: 10%; interlayer adhesion: 8.2 kJ / m² Weight reduction effect: 40%; interlayer adhesion: 2.1 kJ / m² Weight reduction effect: 0; Interlayer adhesion: 6.5 kJ / m²

[0070] Foaming stability test: Foaming stability is determined based on the stability of the consumable wire diameter. The consumable wire diameter fluctuates within 1.75±0.03mm, which is consistent with ordinary consumables. The diameter of the foamed PLA wire from competing products fluctuates between 1.65-1.85mm.

[0071] In summary, this invention greatly improves the production efficiency of PLA lightweight consumables during the printing process, while solving the problems of poor surface effect and unstable weight reduction effect of PLA lightweight consumable printed models. It also optimizes printing parameters, eliminating the need for special adjustment of printing parameters, making it more applicable and suitable for a wider range of scenarios.

[0072] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A lightweight PLA composite material for 3D printing, characterized in that, It comprises the following raw materials by weight percentage: 90%-95% polylactic acid, 2%-5% modified expanded microsphere foaming masterbatch, 0.3%-0.8% antioxidant and 2%-5% plasticizer, wherein the antioxidant includes hindered phenolic antioxidant 1010 and phosphite antioxidant 168; the modified expanded microsphere foaming masterbatch is prepared by surface treatment of foamed microspheres with KH-550 silane coupling agent.

2. The lightweight PLA composite material for 3D printing according to claim 1, characterized in that, The surface treatment conditions include: treatment at 60℃-80℃ for 2-3 hours in a system with an ethanol:water volume ratio of 9:1, and a solid-liquid ratio of 1:8 between the foamed microspheres and KH-550 silane coupling agent. Preferably, the foamed microspheres are selected from polypropylene expanded microsphere foaming masterbatch, polyethylene masterbatch, polyvinyl chloride masterbatch, EVA, POE, TPR, TPV or TPU.

3. The lightweight PLA composite material for 3D printing according to claim 1, characterized in that, The mass ratio of the hindered phenolic antioxidant 1010 to the phosphite antioxidant 168 is (1-3):2; Preferably, the mass ratio of the modified expanded microsphere foaming masterbatch to the hindered phenolic antioxidant 1010 and the phosphite antioxidant 168 is 100:3:

2.

4. The lightweight PLA composite material for 3D printing according to claim 1, characterized in that, The raw materials for the PLA composite material also include a lubricant; the lubricant accounts for 0.5% ± 0.1% of the mass of the raw materials. Preferably, the raw materials of the PLA composite material further include 0.3% ± 0.05% of an antioxidant synergist; the antioxidant synergist is preferably Irganox 1076; Preferably, the plasticizer is selected from ATBC.

5. A lightweight PLA composite material for 3D printing, characterized in that, It comprises the following raw materials by weight percentage: 75%-85% polylactic acid, 2%-5% modified expanded microsphere foaming masterbatch, 0.3%-0.8% antioxidant, 5%-15% elastomer, and 2%-5% plasticizer; the antioxidant includes hindered phenolic antioxidant 1010 and phosphite antioxidant 168; the modified expanded microsphere foaming masterbatch is prepared by surface treatment of foamed microspheres with KH-550 silane coupling agent.

6. The lightweight PLA composite material for 3D printing according to claim 5, characterized in that, The mass ratio of the hindered phenolic antioxidant 1010 to the phosphite antioxidant 168 is (1-3):2; Preferably, the mass ratio of the modified expanded microsphere foaming masterbatch to the hindered phenolic antioxidant 1010 and the phosphite antioxidant 168 is 100:3:

2.

7. The lightweight PLA composite material for 3D printing according to claim 5, characterized in that, The elastomer is selected from thermoplastic polyurethane elastomers, natural rubber and its epoxidized modified products, styrene-based thermoplastic elastomers, bio-based copolyester elastomers (PLBSIs), polycaprolactone (PCL) or polybutylene succinate (PBS). Preferably, the raw materials for the PLA composite material further include a lubricant; the lubricant accounts for 0.5% ± 0.1% of the mass of the raw materials. Preferably, the raw materials of the PLA composite material further include 0.3% ± 0.05% of an antioxidant synergist; the antioxidant synergist is preferably Irganox 1076; Preferably, the plasticizer is selected from ATBC.

8. The method for preparing a lightweight PLA composite material for 3D printing as described in any one of claims 1-4 or 5-7, characterized in that, It includes the following steps: The raw materials are mixed and then extruded into fibers using a screw extruder.

9. The method for preparing lightweight PLA composite material for 3D printing according to claim 8, characterized in that, After the raw materials are melt-blended and water-cooled and granulated, the resulting granules are vacuum-dried, and then melt-blended and water-cooled and drawn into fibers using a single-screw extruder. Preferably, the raw materials are mixed and then melt-blended using a twin-screw extruder. The length-to-diameter ratio of the screw is 35-95, the temperature range is 180℃-220℃, and the die temperature is 200-220℃. Vacuum dried at 80℃ for 4 hours; The material is melt-blended using a single-screw extruder with a screw length-to-diameter ratio of 45, a temperature range of 180℃-220℃, a die temperature of 220℃, and water-cooled drawing.

10. A method for printing 3D products using the FDM method, characterized in that, The lightweight PLA composite material prepared by the preparation method according to any one of claims 8-9 is introduced into an FDM 3D printing equipment and printed directly without a preheating chamber or a closed printing chamber. The nozzle temperature is 190-220℃, the heated bed temperature is 55±1℃, and the extrusion flow rate of the PLA composite material is 0.91-0.98g / s.